Lightweight self-identifying slow-release remediation material for non-aqueous phase contaminants and preparation method and application thereof
Patent Information
- Application Number
- CN202311370394.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-10-20
AI Technical Summary
[0006]本发明的目的是为了克服现有修复技术存在的拖尾反弹、有效利用率低、识别性低等问题,提供一种轻质非水相污染物自识别缓释修复材料及其制备方法和应用
[0054]1、本发明所述的轻质非水相污染物自识别缓释修复材料具备LNAPL相污染物的选择性识别功能,第二包衣层在遇到LNAPL相污染物或高浓度水中油(水相中油含量较高)时,可以发生自溶解,从而启动LNAPL相污染物修复药剂材料释放,实现LNAPL相及时高效净化去除。
Smart Images

Figure CN119858970B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of site pollutant remediation technology, specifically to a lightweight, non-aqueous phase pollutant self-identifying slow-release remediation material, its preparation method, and its application. Background Technology
[0002] Petroleum hydrocarbons, primarily composed of alkanes, cycloalkanes, and aromatics, can leak into the soil and groundwater during production, storage, transportation, and use in the petrochemical industry. This leakage can lead to soil and groundwater contamination and the formation of light non-aqueous oil-bearing phase (LNAPL) layers in the formation. LNAPL contaminants are widely present in petrochemical enterprises; their density is lower than that of groundwater, and during infiltration, they mainly exist in low-permeability areas of the vadose zone or areas with fluctuating groundwater levels. LNAPL contamination layers contain large amounts of highly concentrated, highly toxic, and poorly water-soluble organic pollutants. Their migration and diffusion can cause the expansion of oil pollution plumes in water, making them a high-risk source of soil and groundwater pollution. They can also volatilize, forming organic vapor intrusions that pose significant threats to human health and the ecological environment. Therefore, adopting targeted technologies and materials to achieve timely and efficient removal and diffusion control of LNAPL is of great importance.
[0003] Existing LNAPL remediation treatments mainly include in-situ chemical oxidation, in-situ extraction, and microbial degradation technologies, all of which have engineering application cases both domestically and internationally. In-situ chemical oxidation technology involves injecting remediation agents into LNAPL-contaminated formations under pressure. Through the oxidation reaction between the agent and the pollutants, the LNAPL phase and oil contaminants in the water are purified and removed. For example, patent application CN106269823B discloses a remediation method for soils contaminated with high concentrations of organic matter. The core of this technology is the injected oxidizing agent. However, organic matter in the soil also consumes the oxidizing agent, and LNAPL pollutants fluctuate with groundwater levels. If the injected agent fails to contact the pollutants, it will gradually lose its oxidizing capacity within the multi-component system of the soil, resulting in low effective utilization. In-situ extraction treatment technology typically uses power pumps to generate negative pressure, extracting LNAPL phases and contaminated groundwater to the surface for purification, as seen in patent applications CN110255638A and CN111137941A. This type of extraction treatment technology lacks specificity and often suffers from LNAPL tailing and rebound after remediation. Furthermore, the extracted pollutants still require further purification, resulting in generally high operating costs. Microbial degradation technology primarily targets low-concentration petroleum hydrocarbon pollutants in soil and groundwater. For example, patent application CN107399830A discloses a bioremediation composition technology with delayed-release materials for removing hydrocarbons from contaminated environments. This technology uses multiple bioremediation materials to degrade petroleum hydrocarbons. However, for high-concentration LNAPL phase pollutants, which are highly toxic and have low biochemical properties, the degradation efficiency of petroleum hydrocarbons is low, making it difficult to efficiently remove LNAPL.
[0004] Currently, the remediation materials involved in the aforementioned in-situ chemical oxidation, in-situ extraction treatment, and microbial degradation mainly include chemical oxidants, surface solubilizers, and biostimulants. For example, patent application CN114904906A discloses a non-aqueous liquid pollutant remediation agent, its preparation method, and its application. This mainly uses an ion-pair oxidant composed of inorganic oxidants such as quaternary ammonium salts and persulfates, which is soluble in the non-aqueous phase. However, the oxidation process cannot identify the LNAPL phase, lacking specificity in remediation targets. It is consumed by environmental components such as soil organic matter, making it difficult to achieve full and effective utilization. Patent application CN104773766A discloses a soybean oil-coated nano-iron slurry groundwater pollution remediation reagent and its preparation method. This mainly uses soybean oil encapsulation to protect the nano-iron's antioxidant capacity in air and improve its migration performance in underground pores, without controlling its release capacity. In in-situ extraction treatment technology, injecting surface solubilizers can also be used to promote the effect, as in the patent application... Please refer to CN111215000A, which discloses a surfactant for treating non-aqueous phase pollutants in soil and groundwater. Its main function is to elute and solubilize during in-situ extraction treatment, but it cannot purify and remove LNAPL phase pollutants. CN110759319A discloses a slow-release nano-calcium peroxide material and its preparation method for removing chlorinated hydrocarbons and / or benzene series compounds from groundwater. This material can achieve slow-release of the agent through structural design. Its main function is to stimulate microbial metabolism by increasing the electron donor level through calcium peroxide, thereby remediating low concentrations of organic pollutants in soil and groundwater. However, due to the limited mass transfer effect caused by the need for calcium peroxide to react with water, and the high toxicity of LNAPL, this material is not very effective against LNAPL phase and high concentration pollutants.
[0005] Existing in-situ chemical oxidation, in-situ extraction, and microbial degradation remediation technologies and materials for groundwater can basically meet the requirements for the degradation and removal of water-soluble petroleum hydrocarbon pollutants in groundwater. However, for non-water-soluble non-aqueous petroleum hydrocarbon (LNAPL) pollutants, there are still many problems in terms of remediation and removal capabilities. For example, there are issues such as tailing and rebound, and low effective utilization rates. Furthermore, LNAPL fluctuates vertically or horizontally with the groundwater flow field and water level. This rebound precipitation and fluctuation migration are also covert, making them difficult to detect and treat in a timely manner. Moreover, existing technologies and agents lack efficient identification selectivity. Therefore, there is an urgent need to develop new targeted removal materials. Summary of the Invention
[0006] The purpose of this invention is to overcome the problems of tailing rebound, low effective utilization rate, and low recognition in existing remediation technologies, and to provide a lightweight non-aqueous phase pollutant self-identifying slow-release remediation material, its preparation method, and its application. The lightweight non-aqueous phase pollutant self-identifying slow-release remediation material of this invention is a multi-layered core-shell structured granular material. After being injected into the soil and groundwater of a site, when pollutant migration or tailing rebound leads to the appearance of LNAPL phase pollutants, the lightweight non-aqueous phase pollutant self-identifying slow-release remediation material can automatically identify and initiate the release of its internal remediation agent material, achieving the purification and removal of the LNAPL phase and oil in the water of the contaminated strata.
[0007] To achieve the above objectives, the present invention provides a lightweight non-aqueous pollutant self-identification slow-release remediation material, wherein the self-identification slow-release remediation material has a multi-core-shell structure, wherein the multi-core-shell structure has a core, a first coating layer and a second coating layer distributed sequentially from the inside to the outside.
[0008] The kernel contains repair components;
[0009] The first coating layer has pores and contains a thermosetting resin;
[0010] The second coating layer contains a fat-soluble material.
[0011] Preferably, the diameter of the core is 250-350 μm.
[0012] Preferably, the repair component contains an oxidative repair agent and optional auxiliary agents;
[0013] Preferably, the oxidative remediation agent is selected from one or more of persulfate, potassium permanganate, and peroxide;
[0014] Preferably, the additive is selected from one or more of catalysts, pH adjusters, and solubilizers.
[0015] Preferably, the catalyst is selected from one or more of ferrous sulfate, manganese oxide composite materials, and nano-iron materials;
[0016] Preferably, the pH adjuster is selected from one or more of ferric chloride, ammonium chloride, and aluminum chloride;
[0017] Preferably, the pro-solvent is selected from one or more of triethanolamine soap, polysorbate, and rhamnolipid.
[0018] Preferably, the pore size of the first coating layer is 0.1-10 μm;
[0019] Preferably, the porosity of the first coating layer is 50-70%.
[0020] Preferably, the thickness of the first coating layer is 10-100 μm.
[0021] Preferably, the thermosetting resin is selected from one or more of the following: medium-temperature phenolic resin, linear urea-formaldehyde resin, unsaturated polyester resin, amine-modified epoxy resin, and polymethyl silicone resin.
[0022] Preferably, the thickness of the second coating layer is 10-100 μm.
[0023] Preferably, the fat-soluble material is selected from one or more of fatty acids, paraffin wax, and glycerin;
[0024] Preferably, the fatty acid is selected from C16-C20 fatty acids.
[0025] A second aspect of this invention provides a method for preparing lightweight, non-aqueous pollutant self-identification and sustained-release remediation materials, the method comprising the following steps:
[0026] S1: The repair components are mixed with the binder and then granulated to obtain the core;
[0027] S2: Thermosetting resin and ethanol are mixed to obtain a first coating solution. The first coating solution is used to coat the core to form a first coating layer on the surface of the core.
[0028] S3: Heat the fat-soluble material to obtain a second coating solution, and use the second coating solution to coat the material obtained in step S2 to form a second coating layer on the surface of the first coating layer.
[0029] Preferably, the repair component contains an oxidative repair agent and optional auxiliary agents;
[0030] Preferably, the oxidative remediation agent is selected from one or more of persulfate, potassium permanganate, and peroxide;
[0031] The additive is selected from one or more of the following: catalyst, pH adjuster, and solubilizer.
[0032] Preferably, in step S1, the weight ratio of the repair component to the adhesive is 5-9:1;
[0033] Preferably, the binder is selected from one or more of potassium silicate, phosphate, aluminate, inorganic mortar and diatomaceous earth.
[0034] Preferably, the diameter of the core is 250-350 μm.
[0035] Preferably, in step S2, the volume ratio of thermosetting resin to ethanol is 1-3:1.
[0036] Preferably, the volume ratio of the kernel to the first coating solution is 1-3:1;
[0037] Preferably, the thermosetting resin is selected from one or more of the following: medium-temperature phenolic resin, linear urea-formaldehyde resin, unsaturated polyester resin, amine-modified epoxy resin, and polymethyl silicone resin.
[0038] Preferably, the specific process of step S2 includes:
[0039] Thermosetting resin and ethanol are mixed to obtain a first coating solution. The core is placed in a preheated fluidized bed coating machine, and then the first coating solution is sprayed in for coating. Then, it is dried.
[0040] Preferably, the drying temperature is 70-90℃ and the drying time is 1-2 hours.
[0041] Preferably, in step S2, the thickness of the first coating layer is 10-100 μm;
[0042] Preferably, the pore size of the first coating layer is 0.1-10 μm;
[0043] Preferably, the porosity of the first coating layer is 50-70%;
[0044] Preferably, in step S3, the fat-soluble material is selected from one or more of fatty acids, paraffin, and glycerol;
[0045] Preferably, the fatty acid is selected from C16-C20 fatty acids.
[0046] Preferably, in step S3, the volume ratio of the material obtained in step (2) to the amount of the second coating liquid is 2-5:1.
[0047] Preferably, in step S3, the thickness of the second coating layer is 10-100 μm.
[0048] Preferably, the specific process of step S3 includes:
[0049] The fat-soluble material is heated to obtain a second coating liquid. The material obtained in step S2 is placed in a preheated fluidized bed coating machine, and then the second coating liquid is sprayed in for coating. Then it is dried.
[0050] Preferably, the drying temperature is 30-40℃ and the time is 1-3 hours.
[0051] A third aspect of the present invention provides a lightweight, non-aqueous phase pollutant self-identification and slow-release remediation material prepared by the method described above.
[0052] The fourth aspect of this invention provides the application of the aforementioned lightweight non-aqueous pollutant self-identification slow-release remediation material in the remediation of lightweight non-aqueous pollutants.
[0053] Compared with existing technologies, the lightweight non-aqueous pollutant self-identification and slow-release remediation material of this invention has the following advantages:
[0054] 1. The lightweight non-aqueous phase pollutant self-identification slow-release remediation material of the present invention has the selective identification function of LNAPL phase pollutants. When the second coating layer encounters LNAPL phase pollutants or high concentration of oil in water (high oil content in the aqueous phase), it can undergo self-dissolution, thereby initiating the release of LNAPL phase pollutant remediation agent material, realizing timely and efficient purification and removal of LNAPL phase.
[0055] 2. The first coating layer of the lightweight non-aqueous pollutant self-identification slow-release remediation material of the present invention not only has the function of controlling the release rate of the remediation agent, but is also composed of a hydrophobic and oleophilic thermosetting resin, which can improve the affinity and adhesion of organic pollutants and enhance the targeted removal ability of LNAPL phase and oil pollutants in water.
[0056] 3. The lightweight non-aqueous phase pollutant self-identification slow-release remediation material of the present invention can be combined with in-situ extraction treatment technology. After being injected underground, it can solve the problem of tailing and rebound of LNAPL phase pollutants after extraction treatment. It can also be directly injected into the target formation in sufficient quantity, which can solve the problem of LNAPL pollutants fluctuating with groundwater level, thereby improving LNAPL remediation efficiency.
[0057] 4. The lightweight non-aqueous phase pollutant self-identification slow-release remediation material of the present invention can selectively identify LNAPL phase pollutants, avoid the consumption of remediation materials by the multi-component system of soil and groundwater itself, reduce the amount of remediation agent injected, and effectively improve the utilization rate of the agent. Attached Figure Description
[0058] Figure 1 This is a schematic diagram of the structure of a lightweight, non-aqueous pollutant self-identification and slow-release remediation material according to an embodiment of the present invention.
[0059] Explanation of reference numerals in the attached figures
[0060] 1. Second coating layer 2. First coating layer
[0061] 3 kernels Detailed Implementation
[0062] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0063] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0064] The first aspect of this invention provides a lightweight, non-aqueous pollutant self-identification and slow-release remediation material, in conjunction with reference to [reference needed]. Figure 1 The self-identifying sustained-release repair material has a multi-core-shell structure, which has a core 3, a first coating layer 2 and a second coating layer 1 distributed from the inside to the outside.
[0065] The kernel 3 contains repair components;
[0066] The first coating layer 2 has pores and contains a thermosetting resin;
[0067] The second coating layer 1 contains a fat-soluble material.
[0068] In a preferred embodiment, the core 3 further contains a binder. Using a binder helps maintain the stability of the shape and structure of the core 3.
[0069] More preferably, the diameter of the core 3 is 250-350 μm.
[0070] In a preferred embodiment, the repair component contains an oxidative repair agent and optional adjuvants.
[0071] More preferably, the oxidative remediation agent is selected from one or more of persulfate, potassium permanganate, and peroxide.
[0072] More preferably, the additive is selected from one or more of a catalyst, a pH adjuster, and a solubilizer. The additive is used to enhance the repair effect of the repair material.
[0073] More preferably, the catalyst may be selected from one or more of ferrous sulfate, manganese oxide composite materials, and nano-iron materials;
[0074] More preferably, the pH adjuster may be selected from one or more of ferric chloride, ammonium chloride, and aluminum chloride;
[0075] More preferably, the prosolvent may be selected from one or more of triethanolamine soap, polysorbate, and rhamnolipid.
[0076] In a specific embodiment, when the oxidative remediation agent is selected from persulfate, the auxiliary agent is selected from catalyst and solubilizer.
[0077] In a specific implementation, when the oxidative remediation agent is selected from potassium permanganate, the auxiliary agent is selected from pH adjuster and solubilizer.
[0078] According to a preferred embodiment of the present invention, when the repair component contains an oxidizing repair agent and an auxiliary agent, the weight ratio of the oxidizing repair agent to the auxiliary agent is 1-4:1; specifically, it can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1.
[0079] In a preferred embodiment, the pore size of the first coating layer 2 is 0.1-10 μm.
[0080] In this invention, the pore size of the first coating layer 2 refers to the average pore size, which can be measured by the BET method.
[0081] In a preferred embodiment, the porosity of the first coating layer 2 is 50-70%; specifically, it can be 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 62%, 64%, 66%, 68%, or 70%.
[0082] In a preferred embodiment, the thickness of the first coating layer 2 is 10-100 μm; specifically, it can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 95 μm or 100 μm.
[0083] In a preferred embodiment, the thermosetting resin is selected from one or more of the following: medium-temperature phenolic resin, linear urea-formaldehyde resin, unsaturated polyester resin, amine-modified epoxy resin, and polymethyl silicone resin.
[0084] In a preferred embodiment, the thickness of the second coating layer 1 is 10-100 μm; specifically, it can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm.
[0085] In this invention, the first coating layer 2 can control the release rate of the repair agent and improve the utilization efficiency of the agent. At the same time, the layer is composed of a hydrophobic and oleophilic thermosetting resin, which has the function of promoting the directional removal of oil phase and oil in water of LNAPL, thereby improving the targeted repair efficiency. By reasonably controlling the pore size and porosity of the first coating layer 2, the release rate of the repair agent material can be controlled at the molecular level.
[0086] In a preferred embodiment, the fat-soluble material is selected from one or more of fatty acids, paraffin, and glycerol.
[0087] More preferably, the fatty acid is selected from C16-C20 fatty acids.
[0088] In one specific embodiment, the fatty acid is a C18 fatty acid.
[0089] In this invention, when the second coating layer 1 comes into contact with LNAPL phase or oil contaminants in high-concentration water, the second coating layer 1 can dissolve, thereby automatically recognizing and initiating the release of LNAPL phase contaminant remediation agents in the body. The effective self-recognition and dissolution time in LNAPL phase contaminants is 2-5 minutes.
[0090] The lightweight non-aqueous phase pollutant self-identification slow-release remediation material of the present invention can be combined with in-situ extraction treatment technology. It can be injected underground in the later stage of extraction treatment. When LNAPL phase pollutants rebound and precipitate again, the self-identification slow-release remediation material of the present invention can selectively identify them and undergo shell self-dissolution recognition, thereby initiating the release of LNAPL phase pollutant remediation agent materials and solving the problem of tailing rebound of LNAPL phase pollutants after extraction treatment.
[0091] A second aspect of this invention provides a method for preparing lightweight, non-aqueous pollutant self-identification and sustained-release remediation materials, the method comprising the following steps:
[0092] S1: The repair components are mixed with the binder and then granulated to obtain the core;
[0093] S2: Thermosetting resin and ethanol are mixed to obtain a first coating solution. The first coating solution is used to coat the core to form a first coating layer on the surface of the core.
[0094] S3: Heat the fat-soluble material to obtain a second coating solution, and use the second coating solution to coat the material obtained in step S2 to form a second coating layer on the surface of the first coating layer.
[0095] In a preferred embodiment, the repair component contains an oxidative repair agent and optional adjuvants.
[0096] More preferably, the oxidative remediation agent is selected from one or more of persulfate, potassium permanganate, and peroxide.
[0097] In a preferred embodiment, the additive is selected from one or more of a catalyst, a pH adjuster, and a solubilizer.
[0098] In a specific embodiment, the catalyst may be a transition-activated metal compound, such as one or more selected from ferrous sulfate, manganese oxide composite materials and nano-iron materials; the pH adjuster may be one or more selected from ferric chloride, ammonium chloride and aluminum chloride; and the solubilizer may be one or more selected from triethanolamine soap, polysorbate and rhamnolipid.
[0099] In a preferred embodiment, when the repair component contains an oxidizing repair agent and an auxiliary agent, the weight ratio of the oxidizing repair agent to the auxiliary agent is 1-4:1; specifically, it can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1.
[0100] In a preferred embodiment, in step S1, the weight ratio of the repair component to the adhesive is 5-9:1; specifically, it can be 5:1, 6:1, 7:1, 8:1 or 9:1.
[0101] More preferably, the binder is selected from one or more of potassium silicate, phosphate, aluminate, inorganic mortar and diatomaceous earth.
[0102] In a preferred embodiment, step S1, granulation can be performed on equipment conventionally used in the art, capable of shaping the mixture of repair components and binder. For example, a mixing pelletizer can be used.
[0103] Preferably, the diameter of the core is 250-350μm; specifically, the diameter of the core can be 250μm, 260μm, 270μm, 280μm, 290μm, 300μm, 310μm, 320μm, 330μm, 340μm or 350μm.
[0104] In the method described in this invention, in step S2, the kernel obtained in step S1 is coated with a first coating solution to form a first coating layer on the kernel surface. This first coating layer can control the release rate of the repair agent and improve the utilization efficiency of the agent.
[0105] In the method described in this invention, in order to further improve the sustained-release performance of the self-identifying sustained-release repair material, the dosage relationship between thermosetting resin and ethanol can be reasonably controlled. In a preferred embodiment, in step S2, the volume ratio of thermosetting resin to ethanol is 1-3:1.
[0106] In a preferred embodiment, in step S2, the volume ratio of the core to the first coating liquid is 1-3:1; specifically, it can be 1:1, 1.5:1, 2:1, 2.5:1 or 3:1.
[0107] In a preferred embodiment, the thermosetting resin is selected from one or more of the following: medium-temperature phenolic resin, linear urea-formaldehyde resin, unsaturated polyester resin, amine-modified epoxy resin, and polymethyl silicone resin.
[0108] In a preferred embodiment, step S2 specifically includes:
[0109] Thermosetting resin and ethanol are mixed to obtain a first coating solution. The core is placed in a preheated fluidized bed coating machine, and then the first coating solution is sprayed in for coating. Then, it is dried.
[0110] In a preferred embodiment, in step S2, the preheating temperature is 40-60°C; specifically, it can be 40°C, 45°C, 50°C, 55°C, or 60°C.
[0111] In a preferred embodiment, in step S2, the drying temperature is 70-90°C, and the drying time is 1-2 hours. Specifically, the drying temperature can be 70°C, 75°C, 80°C, 85°C, or 90°C.
[0112] In a preferred embodiment, the coating process in step S2 can be carried out in a fluidized bed coating machine.
[0113] In the method described in this invention, to further improve the sustained-release and repair performance of the self-identifying sustained-release repair material, the thickness, pore size, and porosity of the obtained first coating layer can be reasonably controlled. In a preferred embodiment, the thickness of the first coating layer is 10-100 μm; specifically, it can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 95 μm, or 100 μm. The pore size of the first coating layer is 0.1-10 μm; more preferably 6-8 μm; the porosity of the first coating layer is 50-70%; more preferably 55-65%.
[0114] In the method described in this invention, in step S2, a mixture of thermosetting resin and ethanol is used as the coating liquid. The thermosetting resin, as the main component of the first coating layer 2, has the function of promoting the directional removal of oil phase and oil in water of LNAPL, thereby improving the targeted repair efficiency. The evaporation of ethanol during the drying process gives the first coating layer a certain amount of pores, which further improves the sustained-release performance of the repair material.
[0115] In the method described in this invention, in step S3, the material obtained in step S2 (i.e., the core coated with the first coating layer) is coated with a second coating solution to form a second coating layer on the surface of the first coating layer. When the second coating layer comes into contact with the LNAPL phase or oil contaminants in high-concentration water, it can dissolve, thereby automatically recognizing and initiating the release of LNAPL phase contaminant remediation agents within the body.
[0116] In a preferred embodiment, in step S3, the fat-soluble material is selected from one or more of fatty acids, paraffin, and glycerol.
[0117] More preferably, the fatty acid is selected from C16-C20 fatty acids.
[0118] In a preferred embodiment, in step S3, the volume ratio of the material obtained in step S2 to the amount of the second coating liquid is 2-5:1; specifically, it can be 2:1, 3:1, 4:1 or 5:1.
[0119] In the method described in this invention, in order to further improve the recognition ability of the second coating layer for LNAPL phase contaminants and enable rapid dissolution, the thickness of the second coating layer can be reasonably controlled. In a preferred embodiment, in step S3, the thickness of the second coating layer is 10-100 μm; specifically, it can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, or 100 μm.
[0120] In a preferred embodiment, step S3 specifically includes:
[0121] The fat-soluble material is heated to obtain a second coating solution. The material obtained in step S2 is placed in a preheated fluidized bed coating machine, and then the second coating solution is sprayed in for coating. Then, it is dried.
[0122] In a preferred embodiment, in step S3, the heating temperature is 80-90℃; specifically, it can be 80℃, 81℃, 82℃, 83℃, 84℃, 85℃, 86℃, 87℃, 88℃, 89℃ or 90℃.
[0123] In a preferred embodiment, in step S3, the preheating temperature is 40-60°C; specifically, it can be 40°C, 45°C, 50°C, 55°C, or 60°C.
[0124] In a preferred embodiment, in step S3, the drying temperature is 30-40°C and the time is 1-3 hours.
[0125] In a preferred embodiment, the coating process in step S3 can be carried out in a fluidized bed coating machine.
[0126] A third aspect of the present invention provides a self-identifying sustained-release repair material prepared by the method described above.
[0127] The fourth aspect of this invention provides the application of the self-identifying slow-release remediation material described above in the remediation of lightweight non-aqueous phase pollutants.
[0128] The self-identifying slow-release remediation material described in this invention can be used with in-situ chemical oxidation injection technology. The material is injected into LNAPL-contaminated and fluctuating formations through differential pressure to achieve the purification and removal of LNAPL contaminants. Alternatively, it can be used in conjunction with in-situ extraction treatment technology. In the early stage of LNAPL and oil-in-water remediation, extraction is used, followed by injection of the self-identifying slow-release remediation material to achieve the removal of LNAPL phase contaminants that have rebounded and precipitated.
[0129] The present invention will be described in detail below through embodiments, but the scope of protection of the present invention is not limited thereto.
[0130] Unless otherwise specified, all reagents used in the following examples and comparative examples are commercially available products.
[0131] Example 1
[0132] S1: The repair component and binder (phosphate binder) are mixed at a weight ratio of 5.67:1, and then granulated in a mixing pelletizer at a granulation speed of 180 rpm, a granulation temperature of 30℃, and a granulation time of 30 min to obtain a core with a diameter of 306 μm; wherein, the repair component consists of an oxidizing repair agent (sodium persulfate) and an auxiliary agent, the auxiliary agent being selected from a catalyst (ferrous sulfate) and a solubilizer (triethanolamine soap), and the weight ratio of the oxidizing repair agent to the auxiliary agent is 2.4:1;
[0133] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.86:1 to obtain a first coating solution. The core is placed in a fluidized bed coating machine preheated to 50°C, and then the first coating solution is sprayed in for coating. Then, hot air at 80°C is sprayed in for drying for 1.5 hours, forming a first coating layer on the surface of the core. The volume ratio of the core to the first coating solution is 2:1. The thickness of the first coating layer is 88 μm, the porosity is about 55%, and the pore size is about 6 μm.
[0134] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution. The material obtained in step S2 is placed in a fluidized bed coating machine preheated to 45°C, and then sprayed with the second coating solution for coating. After that, it is sprayed with air at 35°C for 2 hours to form a second coating layer on the surface of the first coating layer. The volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the second coating layer is 42μm.
[0135] Example 2
[0136] S1: The repair component and binder (phosphate binder) are mixed at a weight ratio of 5.67:1, and then granulated in a mixing pelletizer at a granulation speed of 180 rpm, a granulation temperature of 30℃, and a granulation time of 30 min to obtain a core with a diameter of approximately 290 μm. The repair component consists of an oxidizing repair agent (sodium persulfate) and an auxiliary agent. The auxiliary agent is selected from a catalyst (ferrous sulfate) and a solvent (triethanolamine soap). The weight ratio of the oxidizing repair agent to the auxiliary agent is 1.43:1.
[0137] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.86:1 to obtain a first coating solution. The core is placed in a fluidized bed coating machine preheated to 50°C, and then the first coating solution is sprayed in for coating. Then, it is sprayed with hot air at 80°C for drying for 1.5 hours, forming a first coating layer on the surface of the core. The volume ratio of the core to the first coating solution is 2:1. The thickness of the first coating layer is 85 μm, the porosity is about 55%, and the pore size is about 6 μm.
[0138] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution. The material obtained in step S2 is placed in a fluidized bed coating machine preheated to 45°C, and then sprayed with the second coating solution for coating. After that, it is sprayed with air at 35°C for 2 hours to form a second coating layer on the surface of the first coating layer. The volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the second coating layer is 40μm.
[0139] Example 3
[0140] S1: The repair component and binder (phosphate binder) are mixed at a weight ratio of 9:1, and then granulated in a mixing pelletizer at a granulation speed of 180 rpm, a granulation temperature of 30℃, and a granulation time of 30 min to obtain a core with a diameter of approximately 316 μm; wherein, the repair component consists of an oxidizing repair agent (sodium persulfate) and an auxiliary agent, the auxiliary agent being selected from a catalyst (ferrous sulfate) and a solubilizer (triethanolamine soap), and the weight ratio of the oxidizing repair agent to the auxiliary agent is 3.5:1;
[0141] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.86:1 to obtain a first coating solution. The core is placed in a fluidized bed coating machine preheated to 50°C, and then the first coating solution is sprayed in for coating. Then, hot air at 85°C is sprayed in for drying for 1.5 hours, forming a first coating layer on the surface of the core. The volume ratio of the core to the first coating solution is 2:1. The thickness of the first coating layer is 86 μm, the porosity is about 55%, and the pore size is about 6 μm.
[0142] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution. The material obtained in step S2 is placed in a fluidized bed coating machine preheated to 45°C, and then sprayed with the second coating solution for coating. After that, it is sprayed with air at 35°C for 2.5 hours to form a second coating layer on the surface of the first coating layer. The volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the second coating layer is 40 μm.
[0143] Example 4
[0144] S1: The repair component and binder (phosphate binder) are mixed at a weight ratio of 5.67:1, and then granulated in a mixing pelletizer at a granulation speed of 180 rpm, a granulation temperature of 30℃, and a granulation time of 30 min to obtain a core with a diameter of approximately 310 μm. The repair component consists of an oxidizing repair agent (sodium persulfate) and an auxiliary agent. The auxiliary agent is selected from a catalyst (ferrous sulfate) and a solubilizer (triethanolamine soap). The weight ratio of the oxidizing repair agent to the auxiliary agent is 2.4:1.
[0145] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.22:1 to obtain a first coating solution. The core is placed in a fluidized bed coating machine preheated to 50°C, and then the first coating solution is sprayed in for coating. Then, hot air at 90°C is sprayed in for drying for 1 hour, forming a first coating layer on the surface of the core. The volume ratio of the core to the first coating solution is 2.5:1. The thickness of the first coating layer is 72 μm, the porosity is about 61%, and the pore size is about 7 μm.
[0146] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution. The material obtained in step S2 is placed in a fluidized bed coating machine preheated to 45°C, and then sprayed with the second coating solution for coating. After that, it is sprayed with air at 35°C for 2 hours to form a second coating layer on the surface of the first coating layer. The volume ratio of the material obtained in step S2 to the second coating solution is 4:1, and the thickness of the second coating layer is 28μm.
[0147] Example 5
[0148] S1: The repair component and binder (phosphate binder) are mixed at a weight ratio of 5.67:1, and then granulated in a mixing pelletizer at a granulation speed of 180 rpm, a granulation temperature of 30℃, and a granulation time of 30 min to obtain a core with a diameter of approximately 300 μm. The repair component consists of an oxidizing repair agent (sodium persulfate) and an auxiliary agent. The auxiliary agent is selected from a catalyst (ferrous sulfate) and a solvent (triethanolamine soap). The weight ratio of the oxidizing repair agent to the auxiliary agent is 2.4:1.
[0149] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.22:1 to obtain a first coating solution. The core is placed in a fluidized bed coating machine preheated to 50°C, and then the first coating solution is sprayed in for coating. Then, it is sprayed with hot air at 80°C for drying for 1.5 hours, forming a first coating layer on the surface of the core. The volume ratio of the core to the first coating solution is 2.5:1. The thickness of the first coating layer is 71 μm, the porosity is about 62%, and the pore size is about 7 μm.
[0150] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution. The material obtained in step S2 is placed in a fluidized bed coating machine preheated to 45°C, and then sprayed with the second coating solution for coating. After that, it is sprayed with air at 35°C for 2 hours to form a second coating layer on the surface of the first coating layer. The volume ratio of the material obtained in step S2 to the second coating solution is 3.5:1, and the thickness of the second coating layer is 33μm.
[0151] Example 6
[0152] S1: The repair component and binder (potassium silicate binder) are mixed at a weight ratio of 5.67:1, and then granulated in a mixing pelletizer at a granulation speed of 180 rpm, a granulation temperature of 30℃, and a granulation time of 30 min to obtain a core with a diameter of approximately 310 μm. The repair component consists of an oxidizing repair agent (potassium permanganate) and an auxiliary agent. The auxiliary agent is selected from a pH adjuster (ferric chloride) and a solvent promoter (polysorbate). The weight ratio of the oxidizing repair agent to the auxiliary agent is 2.4:1.
[0153] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.86:1 to obtain a first coating solution. The core is placed in a fluidized bed coating machine preheated to 50°C, and then the first coating solution is sprayed in for coating. Then, hot air at 85°C is sprayed in for drying for 1 hour, forming a first coating layer on the surface of the core. The volume ratio of the core to the first coating solution is 2:1. The thickness of the first coating layer is 91 μm, the porosity is about 56%, and the pore size is about 7 μm.
[0154] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution. The material obtained in step S2 is placed in a fluidized bed coating machine preheated to 45°C, and then sprayed with the second coating solution for coating. After that, it is sprayed with air at 35°C for 2 hours to form a second coating layer on the surface of the first coating layer. The volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the second coating layer is 40μm.
[0155] Example 7
[0156] S1: The repair component and binder (potassium silicate binder) are mixed at a weight ratio of 5.67:1, and then granulated in a mixing pelletizer at a granulation speed of 180 rpm, a granulation temperature of 30℃, and a granulation time of 30 min to obtain a core with a diameter of approximately 305 μm. The repair component consists of an oxidizing repair agent (potassium permanganate) and an auxiliary agent. The auxiliary agent is selected from a pH adjuster (ferric chloride) and a solvent promoter (polysorbate). The weight ratio of the oxidizing repair agent to the auxiliary agent is 1.43:1.
[0157] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.86:1 to obtain a first coating solution. The core is placed in a fluidized bed coating machine preheated to 50°C, and then the first coating solution is sprayed in for coating. Then, hot air at 80°C is sprayed in for drying for 1.5 hours, forming a first coating layer on the surface of the core. The volume ratio of the core to the first coating solution is 2:1. The thickness of the first coating layer is 90 μm, the porosity is about 56%, and the pore size is about 7 μm.
[0158] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution. The material obtained in step S2 is placed in a fluidized bed coating machine preheated to 45°C, and then sprayed with the second coating solution for coating. After that, it is sprayed with air at 40°C for 2 hours to form a second coating layer on the surface of the first coating layer. The volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the second coating layer is 40μm.
[0159] Example 8
[0160] S1: The repair component and binder (potassium silicate binder) are mixed at a weight ratio of 9:1, and then granulated in a mixing pelletizer at a granulation speed of 180 rpm, a granulation temperature of 30℃, and a granulation time of 30 min to obtain a core with a diameter of approximately 290 μm. The repair component consists of an oxidizing repair agent (potassium permanganate) and an auxiliary agent. The auxiliary agent is selected from a pH adjuster (ferric chloride) and a solvent promoter (polysorbate). The weight ratio of the oxidizing repair agent to the auxiliary agent is 3.5:1.
[0161] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.86:1 to obtain a first coating solution. The core is placed in a fluidized bed coating machine preheated to 50°C, and then the first coating solution is sprayed in for coating. Then, it is sprayed with hot air at 85°C for drying for 1.5 hours, forming a first coating layer on the surface of the core. The volume ratio of the core to the first coating solution is 2:1. The thickness of the first coating layer is 90 μm, the porosity is about 50%, and the pore size is about 7 μm.
[0162] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution. The material obtained in step S2 is placed in a fluidized bed coating machine preheated to 45°C, and then sprayed with the second coating solution for coating. After that, it is sprayed with air at 35°C for 2 hours to form a second coating layer on the surface of the first coating layer. The volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the second coating layer is 40μm.
[0163] Example 9
[0164] S1: The repair component and binder (potassium silicate binder) are mixed at a weight ratio of 5.67:1, and then granulated in a mixing pelletizer at a granulation speed of 180 rpm, a granulation temperature of 30℃, and a granulation time of 30 min to obtain a core with a diameter of approximately 308 μm. The repair component consists of an oxidizing repair agent (potassium permanganate) and an auxiliary agent. The auxiliary agent is selected from a pH adjuster (ferric chloride) and a solvent promoter (polysorbate). The weight ratio of the oxidizing repair agent to the auxiliary agent is 2.4:1.
[0165] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.22:1 to obtain a first coating solution. The core is placed in a fluidized bed coating machine preheated to 50°C, and then the first coating solution is sprayed in for coating. Then, hot air at 85°C is sprayed in for drying for 1.5 hours, forming a first coating layer on the surface of the core. The volume ratio of the core to the first coating solution is 2.5:1. The thickness of the first coating layer is 70 μm, the porosity is about 60%, and the pore size is about 7 μm.
[0166] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution. The material obtained in step S2 is placed in a fluidized bed coating machine preheated to 45°C, and then sprayed with the second coating solution for coating. After that, it is sprayed with air at 35°C for 2.5 hours to form a second coating layer on the surface of the first coating layer. The volume ratio of the material obtained in step S2 to the second coating solution is 3:1, and the thickness of the second coating layer is 45μm.
[0167] Example 10
[0168] S1: The repair component and binder (potassium silicate binder) are mixed at a weight ratio of 5.67:1, and then granulated in a mixing pelletizer at a granulation speed of 180 rpm, a granulation temperature of 30℃, and a granulation time of 30 min to obtain a core with a diameter of approximately 295 μm. The repair component consists of an oxidizing repair agent (potassium permanganate) and an auxiliary agent. The auxiliary agent is selected from a pH adjuster (ferric chloride) and a solvent promoter (polysorbate). The weight ratio of the oxidizing repair agent to the auxiliary agent is 2.4:1.
[0169] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.22:1 to obtain a first coating solution. The core is placed in a fluidized bed coating machine preheated to 50°C, and then the first coating solution is sprayed in for coating. Then, it is sprayed with hot air at 90°C for drying for 1.5 hours, forming a first coating layer on the surface of the core. The volume ratio of the core to the first coating solution is 2.5:1. The thickness of the first coating layer is 70 μm, the porosity is about 63%, and the pore size is about 7 μm.
[0170] S3: The fat-soluble material (composed of paraffin and stearic acid in a volume ratio of 3:1) is heated to 90°C to obtain a second coating solution. The material obtained in step S2 is placed in a fluidized bed coating machine preheated to 45°C, and then sprayed with the second coating solution for coating. Then, it is sprayed with air at 35°C for 3 hours to dry, forming a second coating layer on the surface of the first coating layer. The volume ratio of the material obtained in step S2 to the second coating solution is 3.5:1, and the thickness of the second coating layer is 30μm.
[0171] Comparative Example 1
[0172] S1: The repair component and binder (phosphate binder) are mixed at a weight ratio of 5.67:1, and then granulated in a mixing pelletizer at a granulation speed of 180 rpm, a granulation temperature of 30℃, and a granulation time of 30 min to obtain a core with a diameter of 300 μm; wherein, the repair component consists of an oxidizing repair agent (sodium persulfate) and an auxiliary agent, the auxiliary agent being selected from a catalyst (ferrous sulfate) and a solvent (triethanolamine soap), and the weight ratio of the oxidizing repair agent to the auxiliary agent is 2.4:1;
[0173] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.86:1 to obtain a first coating solution. The core is placed in a fluidized bed coating machine preheated to 50°C, and then the first coating solution is sprayed in for coating. Then, hot air at 80°C is sprayed in for drying for 1.5 hours to form a first coating layer on the surface of the core. The volume ratio of the core to the first coating solution is 2:1. The thickness of the first coating layer is 85 μm, the porosity is about 56%, and the pore size is about 7 μm.
[0174] Comparative Example 2
[0175] S1: The repair component and binder (potassium silicate binder) are mixed at a weight ratio of 5.67:1, and then granulated in a mixing pelletizer at a granulation speed of 180 rpm, a granulation temperature of 30℃, and a granulation time of 30 min to obtain a core with a diameter of approximately 305 μm. The repair component consists of an oxidizing repair agent (potassium permanganate) and an auxiliary agent. The auxiliary agent is selected from a pH adjuster (ferric chloride) and a solvent promoter (polysorbate). The weight ratio of the oxidizing repair agent to the auxiliary agent is 2.4:1.
[0176] S2: A thermosetting resin (amine-modified epoxy resin) and ethanol are mixed at a volume ratio of 1.86:1 to obtain a first coating solution. The core is placed in a fluidized bed coating machine preheated to 50°C, and then the first coating solution is sprayed in for coating. Then, hot air at 85°C is sprayed in for drying for 1 hour, forming a first coating layer on the surface of the core. The volume ratio of the core to the first coating solution is 2:1. The thickness of the first coating layer is 90 μm, the porosity is about 56%, and the pore size is about 7 μm.
[0177] Test case
[0178] 1. The sustained-release performance and LNAPL phase pollutant removal capacity of the products obtained in Examples 1-5 and Comparative Example 1 were tested. The test procedure is as follows:
[0179] Add 50g of uncontaminated soil and 500mL of groundwater to a 1000mL beaker, and add 5g of the sample to be tested to the beaker. The sample floats on the water surface. The sulfur content in the water is determined by combustion neutralization method at 1h, 4h, 12h and 20h. Then, 1mL of petroleum ether is added at 24h, and the sulfur content in the water is determined by combustion neutralization method at 25h and 26h. At 48h, the petroleum ether content in the water is determined by extraction, and the removal rate of LNAPL phase pollutant (petroleum ether) is calculated.
[0180] The test results are shown in Table 1. Compared with the comparative example, before the petroleum ether LNAPL phase pollutant was added, the oxidizing remediation agent in the product obtained by the example was not released. After the petroleum ether LNAPL phase pollutant was added, the product obtained by the example underwent self-identification shell dissolution, and the effective sulfur-containing remediation component was rapidly released. The pollutant removal rate was detected to be ≥87.2%. In contrast, the sulfur-containing remediation component of the product obtained in the comparative example was naturally released after addition. It was consumed by the reducing components of the soil and groundwater itself in the early stage. After the pollutant was added, its removal rate was about 41.6%, and its effectiveness was significantly lower.
[0181] Table 1
[0182]
[0183] 2. The sustained-release performance and LNAPL phase pollutant removal capacity of the products obtained in Examples 6-10 and Comparative Example 2 were tested. The test procedure is as follows:
[0184] Add 50g of uncontaminated soil and 500mL of groundwater to a 1000mL beaker, then add 5g of the sample to be tested into the beaker. The sample is dissolved in the water. The manganese content in the water is determined by atomic absorption spectrophotometry at 1h, 4h, 12h, and 20h. Then, 1mL of petroleum ether is added at 24h, and the manganese content in the water is determined by atomic absorption spectrophotometry at 25h and 26h. At 48h, the petroleum ether content in the water is determined by extraction. The LNAPL phase pollutant removal rate is calculated.
[0185] The test results are shown in Table 2. Compared with Comparative Example 2, in Examples 6-10, the oxidative remediation agent in the products obtained before the petroleum ether LNAPL phase pollutant was added was not released. After the petroleum ether LNAPL phase pollutant was added, the products obtained in the examples underwent self-identification shell dissolution, and the manganese-containing effective remediation component was rapidly released, with a pollutant removal rate of ≥85.6%. In contrast, the manganese-containing remediation component in the products of the comparative examples was naturally released after addition and was consumed by the reducing components of the soil and groundwater itself in the early stage. After the pollutant was added, its removal rate was about 65.0%, and its effectiveness was significantly lower.
[0186] Table 2
[0187]
[0188] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A lightweight, non-aqueous pollutant self-identification and slow-release remediation material, characterized in that, The self-identifying sustained-release repair material has a multi-core-shell structure, which has a core (3), a first coating layer (2), and a second coating layer (1) distributed sequentially from the inside to the outside. The core (3) contains repair components; the diameter of the core (3) is 250-350 μm. The first coating layer (2) has pores and contains a thermosetting resin; The second coating layer (1) contains a fat-soluble material; the thickness of the second coating layer (1) is 10-100 μm; The repair component contains an oxidizing agent and an auxiliary agent; the oxidizing agent is selected from one or more of persulfate, potassium permanganate, and peroxide; the auxiliary agent is selected from one or more of catalyst, pH adjuster, and solubilizer; the catalyst is selected from one or more of ferrous sulfate, manganese oxide composite material, and nano-iron material; the pH adjuster is selected from one or more of ferric chloride, ammonium chloride, and aluminum chloride; the solubilizer is selected from one or more of triethanolamine soap, polysorbate, and rhamnolipid. The first coating layer (2) has a pore size of 0.1-10 μm; the first coating layer (2) has a porosity of 50-70% and a thickness of 10-100 μm. The thermosetting resin is selected from one or more of the following: medium-temperature phenolic resin, linear urea-formaldehyde resin, unsaturated polyester resin, amine-modified epoxy resin and polymethyl silicone resin. The fat-soluble material is selected from one or more of fatty acids, paraffin, and glycerol.
2. The lightweight non-aqueous pollutant self-identification slow-release remediation material according to claim 1, characterized in that, The fatty acids are selected from C16-C20 fatty acids.
3. A method for preparing the lightweight non-aqueous pollutant self-identification and slow-release remediation material according to any one of claims 1-2, characterized in that, The method includes the following steps: S1: The repair components are mixed with the binder and then granulated to obtain the core; S2: Thermosetting resin and ethanol are mixed to obtain a first coating solution. The first coating solution is used to coat the core to form a first coating layer on the surface of the core. S3: Heat the fat-soluble material to obtain a second coating solution, and use the second coating solution to coat the material obtained in step S2 to form a second coating layer on the surface of the first coating layer.
4. The method according to claim 3, characterized in that, In step S1, the weight ratio of the repair component to the adhesive is 5-9:
1.
5. The method according to claim 3, characterized in that, The binder is selected from one or more of potassium silicate, phosphate, aluminate, inorganic mortar and diatomaceous earth.
6. The method according to any one of claims 3-5, characterized in that, In step S2, the volume ratio of thermosetting resin to ethanol is 1-3:
1.
7. The method according to claim 6, characterized in that, The volume ratio of the core to the first coating solution is 1-3:
1.
8. The method according to claim 3, characterized in that, The specific process of step S2 includes: Thermosetting resin and ethanol are mixed to obtain a first coating solution. The core is placed in a preheated fluidized bed coating machine, and then the first coating solution is sprayed in for coating. Then, it is dried.
9. The method according to claim 8, characterized in that, The drying temperature is 70-90℃, and the time is 1-2 hours.
10. The method according to claim 3, characterized in that, In step S3, the volume ratio of the material obtained in step S2 to the amount of the second coating liquid is 2-5:
1.
11. The method according to claim 3, characterized in that, The specific process of step S3 includes: The fat-soluble material is heated to obtain a second coating solution. The material obtained in step S2 is placed in a preheated fluidized bed coating machine, and then the second coating solution is sprayed in for coating. Then, it is dried.
12. The method according to claim 11, characterized in that, The drying temperature is 30-40℃, and the time is 1-3 hours.
13. The application of the lightweight non-aqueous pollutant self-identification slow-release remediation material according to any one of claims 1-2 in the remediation of lightweight non-aqueous pollutants.
Citation Information
Patent Citations
Soybean oil coated nano-iron slurry groundwater pollution remediation reagent and preparation method thereof
CN104773766A
A method for remediating soil contaminated with high concentrations of organic matter
CN106269823B
Bioremediation composition with a time release material for removing hydrocarbons from contaminated environments
CN107399830A
In-situ extraction processing system and method for polluted underground water containing non-aqueous phase liquid
CN110255638A
Sustained-release nano-calcium peroxide materials, preparation thereof, and method for removing chlorohydrocarbon and / or benzene series from underground water through sustained-release nano-calcium peroxide materials
CN110759319A